Shotgun Glycomics Identifies Tumor-Associated Glycan Ligands Bound by an Ovarian Carcinoma-Specific Monoclonal Antibody. Issue 1 (December 2017) - Liau, B.; Tan, B.; Teo, G.; Zhang, P.; Choo, A.; Rudd, P.
Abstract Cancers display distinctive carbohydrate molecules (glycans) on their surface proteins and lipids. mAb A4, an in-house generated monoclonal IgM antibody, is capable of distinguishing malignant ovarian carcinoma cells from benign ovarian epithelia by binding specifically to cancer cell-associated glycans. However, the structural details of the glycan targets of mAb A4 have been elusive. Here we developed a novel approach of isolating and fractionating glycan molecules released from glycoproteins in cancer cell lysates using HILIC-UPLC, and used them as probes on a microarray for affinity-based identification of the binding targets, allowing full-size, difficult to synthesize, cancer-associated glycans to be directly studied. As a result of this "shotgun" glycomics approach, we corroborate the previously assigned specificity of mAb A4 by showing that mAb A4 binds primarily to large (>15 glucose units), sialylated N-glycans containing the H-type 1 antigen (Fuc-α1, 2-Gal-β1, 3-GlcNAc). Although mAb A4 was also capable of directly binding to type 1 N-acetyl-lactosamine, this epitope was mostly shielded by sialylation and thus relatively inaccessible to binding. Knowledge of the structure of mAb A4 antigen will facilitate its clinical development as well as its use as a diagnostic biomarker.